2017
DOI: 10.1007/s00300-017-2139-7
|View full text |Cite|
|
Sign up to set email alerts
|

Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome

Abstract: invertebrate herbivory on dwarf birch (Betula glandulosa-nana 1 complex) increases with temperature and precipitation across the tundra biome ' Polar biology, vol. 40, no. 11, pp. 2265-2278. DOI: 10.1007%2Fs00300-017-2139 Digital Object Identifier (DOI): 10.1007%2Fs00300-017-2139-7 Link: Link to publication record in Edinburgh Research Explorer Document Version: Peer reviewed version Published In: Polar biology General rightsCopyright for the publications made accessible via the Edinburgh Research Explorer is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 61 publications
7
63
0
Order By: Relevance
“…While our study includes mammalian and avian herbivores, some of which are functionally convergent, to fully understand herbivore functional diversity, non-vertebrate herbivores should also be considered. Invertebrate herbivory is widespread across the Arctic tundra (Barrio et al 2017) and can interact with vertebrate herbivory (Olofsson et al 2013, Biuw et al 2014). Patterns of trophic functional diversity may only be fully understood by including both invertebrate and vertebrate herbivores in the same analysis.…”
Section: Diversity Patternsmentioning
confidence: 99%
“…While our study includes mammalian and avian herbivores, some of which are functionally convergent, to fully understand herbivore functional diversity, non-vertebrate herbivores should also be considered. Invertebrate herbivory is widespread across the Arctic tundra (Barrio et al 2017) and can interact with vertebrate herbivory (Olofsson et al 2013, Biuw et al 2014). Patterns of trophic functional diversity may only be fully understood by including both invertebrate and vertebrate herbivores in the same analysis.…”
Section: Diversity Patternsmentioning
confidence: 99%
“…Barrio et al (2017) and Koltz et al (2018a), despite having vastly different research approaches, reached similar conclusions about low impacts of invertebrate herbivory, specifically direct consumption of live plant biomass, on plant damage and nutrient cycling. Barrio et al (2017) assessed invertebrate herbivory on over 30,000 birch leaves (Betula sp.) that were collected across the Arctic using standardized protocols.…”
Section: Biotic Interactions and Ecosystem Effectsmentioning
confidence: 72%
“…In fact, Barrio et al (2017) already demonstrated this. Their leaf samples were collected from 56 locations between 2008 and 2015.…”
Section: Biotic Interactions and Ecosystem Effectsmentioning
confidence: 81%
See 2 more Smart Citations